Children of darkness and light : Lori Vallow and Chad Daybell : a story of murderous faith - Hellis, Lori, 1956- (Pegasus Crime, 2024)
It all started when Lori Vallow met Chad Daybell at a doomsday prepper event. Their story grew like a wildfire that creates its own weather, and what happened next will shock even the most experienced true crime reader. Clinging to and manipulating one another, Lori Vallow and Chad Daybell believed the return of Jesus Christ was imminent and that God had chosen them to lead the 144,000 and usher in the new millennium. When the people closest to them began dying, it became clear they would stop at nothing to be together and fulfill their mission. When the bodies of Lori's missing children--J.J. and Tylee--were discovered in Chad's backyard, the strange and complex story of their fundamentalist Mormon beliefs were revealed in all their true horror.